A UNIQUENESS THEOREM FOR DIRAC SYSTEM - Ic, Unal (Editura Bibliotheca-Bibliotheca Publ House, 2020)
In this paper, we solve inverse problem for Dirac System. Especially, we show that it is possible to obtain the uniqueness of the potential function by using spectrums.
Keywords: Dirac Equation; uniqueness theorem; spectrum